Dependence of sports results on data of physical development, morphofunctional and special power preparedness of weight-lifters at the stage of initial preparation - Eugene Bugaev (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the establishment of nature of the interrelation between sports results of weight-lifters and level of their special physical and morphofunctional preparedness. Material & Methods: 48 sportsmen of group of initial preparation of the first year of training were involved to the experiment. The research was conducted on the basis of the chair of weightlifting and boxing of Kharkov state academy of physical culture and CYSS "HTZ". Results: the correlation between indicators of morphofunctional, high-speed and power and special (competitive) preparedness of weight-lifters is revealed at the stage of initial preparation. The conducted research shows that the result of competitive exercises of the sportsmen, specializing in weightlifting at the stage of initial preparation, depends on power and high-speed and power preparedness. Conclusions: it is established that the correlation between results of competitive exercises and jumps uphill from the place, in length from the place, run on 30 m can demonstrate the interrelation of power and high-speed and power preparedness of the sportsmen, specializing in weightlifting at the stage of initial preparation.